Strategi Manajemen Pemasaran Pendidikan di SDN Kuripan Lor 01 Pekalongan Jawa Tengah - Aan Fadia Annur; Putri Maghfiroh; Milatunnisa’ Milatunnisa’; Amelia Novitasari; Anik Ma’rifat (STKIP Pesisir Selatan, 2026)
Education is one of the most important things in life. Competition between educational institutions is currently getting tighter. An educational institution must be as active as possible in marketing its institution to attract students and gain public trust. This study aims to analyze the education marketing management strategy at SDN Kuripan Lor 01, identify the implementation of marketing management, and the impact of the implementation of education marketing management. This research uses a qualitative approach, with a qualitative descriptive method. Data were obtained through field observations and direct interviews with the principal. The results showed that the strategies include promotion through social media, improving service quality, and differentiating themselves by showing students' achievements. The implementation of education marketing management at SDN 01 Kuripan Lor is carefully designed through planning from the PPDB committee and predetermined marketing steps. The implementation of the marketing strategy is in accordance with the plan. The resulting impacts include increased interest in student enrollment, community support and the loyalty of parents of learners, which is reflected in their recommendations to others.